2000
DOI: 10.1007/s002530000410
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of xyn3 gene expression in Trichoderma reesei PC-3-7

Abstract: The characteristics of regulation of the gene encoding the third xylanase (Xyn III) of a filamentous fungus, Trichoderma reesei PC-3-7, were studied by Northern blot analysis. A partial DNA sequence (185 bp) of the xyn3 gene was obtained by PCR amplification of genomic DNA of T. reesei PC-3-7 and sequenced. This xyn3 gene fragment was used as a probe for Southern and Northern blot analysis. The expression of the xyn3 gene was regulated at the transcriptional level. The xyn3 mRNA was expressed in mycelia of T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 0 publications
4
28
1
1
Order By: Relevance
“…Probable xylanase inducers are xylobiose, L-arabinose, and cellulose. Others are lactose, which is often used in the industries for the production of hydrolytic enzymes, and sophorose, which was reported as the most powerful xylanase inducer (Chaudhuri and Sahai 1994;Xu et al 2000;Xiong et al 2004). Possible explanations for these contrasting observations could be differences in the physiological and metabolic properties of the various organisms used, the type of fermentation (SSF or SMF), or more importantly, the composition of the fermentation media including the carbon sources (soluble carbon or lignocellulosic sources) (Kulkarni et al 1999).…”
Section: Effect Of Additional Carbon Sources On Xylanase Production Bmentioning
confidence: 99%
“…Probable xylanase inducers are xylobiose, L-arabinose, and cellulose. Others are lactose, which is often used in the industries for the production of hydrolytic enzymes, and sophorose, which was reported as the most powerful xylanase inducer (Chaudhuri and Sahai 1994;Xu et al 2000;Xiong et al 2004). Possible explanations for these contrasting observations could be differences in the physiological and metabolic properties of the various organisms used, the type of fermentation (SSF or SMF), or more importantly, the composition of the fermentation media including the carbon sources (soluble carbon or lignocellulosic sources) (Kulkarni et al 1999).…”
Section: Effect Of Additional Carbon Sources On Xylanase Production Bmentioning
confidence: 99%
“…The PC-3-7 strain, which exhibits increased cellulase activity under inducing conditions, has been used as a model of cellulase induction in our laboratory. [20][21][22] This mutant was developed following several rounds of random mutagenesis. 23,24) During screening for hyper-cellulolytic strains, we found that this strain exhibited an absence of carbon catabolite repression, and that it produced high amounts of cellulases during induction by cellulose, sophorose, and the monosaccharide L-sorbose.…”
Section: Identification Of Major Facilitator Transporters Involved Inmentioning
confidence: 99%
“…While the cellulases of T. reesei are known to be coordinately regulated by cellulose, lactose, and the ␤-1,2-diglucoside sophorose (8,9), differences in the induction of the xylanases were reported: expression of xyn1 is induced by Dxylose, whereas expression of xyn2 is induced by xylobiose and the cellulase-inducing carbohydrates cellulose and sophorose (10). xyn3 expression was found only in a mutant strain (T. reesei PC-3-7) and was induced only by cellulase inducers and not by D-xylose (11). No data on the expression of xyn4 are available.…”
mentioning
confidence: 99%